Dual function projective synchronization of fractional order complex chaotic systems - Yadav V.K.; Srikanth N.; Das S. (My University, 2025)
In this article the dual function projective synchronization among various fractional order complex chaotic systems is investigated using active control technique. Two master systems and two response (salve) systems with control functions are taken for dual function projective synchronization. The control functions are designed with the help of active control technique. The fractional order complex T and complex Lu systems are taken to illustrate synchronization process. The fractional derivative is described in Caputo derivative sense. Numerical simulation and graphical results are presented to demonstrate the effectiveness of the method. © 2016 Elsevier GmbH